Evaluation of Healthy Lifestyle Behavior of Family Physicians and Lifestyle Medicine in Their Clinical Practice - Özden Gökdemir; Hasan Kazdağlı; Makbule İlgi Şemin (Gazi Medical Journal)
Objective: This study aimed to assess the healthy lifestyle behavior of family physicians (FPs) and their engagement in lifestyle medicine practices within their clinical practice. Methods: An online questionnaire was developed to collect responses from FPs between July 2018 and August 2019. A descriptive and correlational design was employed. The questionnaire consisted of two parts: “personal information of participants” and “the Healthy Lifestyle Behavior Scale-II”. The survey was conducted using an e-survey platform, and targeted a convenience sample of FPs from eight countries in a cross-sectional study. Participants were provided with information about the survey length, data storage procedures, duration of storage, the identity of the investigators, and the purpose of the study. Results: The study included 131 FPs, with a higher proportion of male participants. The frequency of smoking was found to be significantly higher among Turkish FPs (p=0.013). However, no statistically significant difference was observed among FPs in terms of the total score on the scale or the scores on the six dimensions. Conclusion: The majority of FPs expressed a desire for further education, suggesting a need to incorporate educational interventions into medical school curricula. Additionally, well-structured web-based massive open online courses could serve a solution to meet the educational needs of FPs in the realm of healthy lifestyle behaviors and lifestyle medicine practices.